Mendorong Diri ke Masa Depan: Psikoedukasi Meningkatkan Keinginan Berpendidikan Lanjut pada Remaja Anak Pekerja Migran Indonesia di Desa Binaan Bulak Indramayu - Adhissa Qonita; Reny Rustyawati; Ratna Dyah Suryaratri; Deasyanti (Universitas Negeri Jakarta, 2025)
This year's community service was given in a village assisted by Universitas Negeri Jakarta (UNJ) located in Jatibarang Indramayu called Bulak Village. This village is a village that contributes quite a lot in sending Indonesian migrant workers (PMI) abroad. This makes many teenagers who have parents who work as PMI. Analyses conducted by UNJ's Institute for Research and Community Service (LPPM) found that the education level in the village is quite low. Most residents in Bulak Village are primary school graduates and up to the latest data only about 5-10% of residents are college graduates. Many teenagers prefer to work directly as Indonesian Migrant Workers who have not been accompanied by education or the desire to develop skills as preparation. Therefore, this community service is given so that adolescents understand their potential so that they know the fields that are their strengths. This self-understanding will be accompanied by knowledge about achievement motivation so that they can encourage themselves to have the desire to have further education or develop their abilities as preparation for the future. Modules will be compiled by experts in the field of psychology which will be adjusted to the needs and age of participants. It is hoped that with this activity teenagers can recognise themselves and encourage themselves to get a higher education.